The Influence of Banking Risk on Efficiency: The Moderating Role of Inflation Rate - Amalia Ilmiani; Meliza Meliza (Indonesian Journal of Economics, Social, and Humanities, 2022)
The increasing business activities of state-owned banks in Indonesia increases risks. This circumstance can impact the level of state-owned banks’ efficiency. Thus, this research analyses the influence of banking risks on the state-owned banks’ efficiency in Indonesia from 2016 to 2019. Moreover, inflation as one of the macroeconomic factors may also affect the relationship between banking risks and efficiency; hence, this research also examines the inflation role as a moderating variable of this relationship. The samples of this research are all state-owned banks in Indonesia. Ordinary Least Squares (OLS) regression analysis shows that liquidity risk and credit risk have positive and significant influences on efficiency. However, inflation as a moderating variable has no significant influence on efficiency. Inflation also fails to moderate the relationship between liquidity risk and efficiency of state-owned banks in Indonesia. Nevertheless, inflation successful moderates the relationship between credit risk and efficiency.